Review Artikel: Formulasi Tablet Menggunakan Metode Granulasi Basah - Ni’matul Fauziah; Miftahul Maulidiyah; Silvia Nur Diana Putri; Heni Amilia Putri; Ferdiana Putri Veronica; Anisya’ Khusnul Khotimah; Renny Anggrayni; Dewi Rahmawati; Yani Ambari (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Tablets are one of the most commonly used solid dosage forms of medicine in the pharmaceutical industry. The granulation process commonly used in making tablets is the wet granulation process. The operation method includes mixing the active ingredients and excipients, adding a binder liquid, forming granules, drying and sieving. The methods used in this research are literature research, journal reviews, and analysis of relevant papers carried out during the 2015-2023 period. The aim of this literature study is to determine the process, advantages, limitations and application of wet granulation in the pharmaceutical industry. Based on the results of a literature study, tablet production using the wet granulation method was proven to be an effective technique and is widely used for the production of tablet formulations.